Internalisasi nilai religius melalui mujahadah shalawat wahidiyah dalam pembentukan karakter siswa - Asep Rahmatullah (Al-Liqo: Jurnal Pendidikan Islam, 2026)
This study examines the internalization of religious values through Mujahadah Shalawat Wahidiyah in shaping students’ character at Wahidiyah Senior High School, Kediri, East Java. Using a qualitative case study approach, data were collected through participatory observation, interviews with six informants, and documentation. The findings reveal that Mujahadah Shalawat Wahidiyah promotes key religious values, including sincerity, patience, honesty (siddiq), trustworthiness, and tabligh. The internalization process occurs through value transformation, value transaction, and transinternalization, supported by shalawat recitation, social interaction, and spiritual experiences. Students who regularly participate demonstrate improved emotional stability, prayer discipline, self-control, respectful communication, and social awareness. The study concludes that Mujahadah Shalawat Wahidiyah effectively strengthens students’ religious character by integrating cognitive, affective, and psychomotor dimensions while offering a practical model for spirituality-based character education in secondary schools.